Carbon dioxide capture and conversion advanced materials and processes - Nanda, Sonil; Vo, Dai-Viet N.; Nguyen, Van-Huy (Chemical engineer) (Elsevier, 2022)
Carbon Dioxide Capture and Conversion: Advanced Materials and Process provides information about the fundamental principles and recent development of various methods and processes for CO2 mitigation and transformation.